The Vikings, victims of their own success? A selective view on Viking research and its dissemination - Croix, Sarah (Danish Journal of Archaeology, 2015)
The Viking age as a time of adventures and violence never ceases to fascinate the public. Both aspects remain central to the definitions of the period which can be found in recent introductions to the topic. Those definitions, developed in Western Europe and applied to the events taking place in this region, are currently being challenged by scholars arguing for the greater significance of economic, political and social developments on a broader scale, beyond the strict agency of individuals of Scandinavian origin. This discussion raises the question of the participation of different regions in the Viking phenomenon and their visibility in the research history. While Viking studies can benefit from this debate thanks to new perspectives on the crosscultural dynamics of the Viking world, generalizations and excessive broadening may potentially lead the concept to lose its meaning. Therefore, we need to retain the focus on the specificities of the Viking age as a particular set of phenomena under the broader scope of contemporary pan-European historical processes and to pursue our research objectives independently from the desires and pre-conceptions of the public.